2020
DOI: 10.3390/nu12020424
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Ubiquinol on Hematological and Inflammatory Signaling during Exercise

Abstract: Strenuous exercise (any activity that expends six metabolic equivalents per minute or more causing sensations of fatigue and exhaustion to occur, inducing deleterious effects, affecting negatively different cells), induces muscle damage and hematological changes associated with high production of pro-inflammatory mediators related to muscle damage and sports anemia. The objective of this study was to determine whether short-term oral ubiquinol supplementation can prevent accumulation of inflammatory mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…> 1 month) on EGF in older men. However, Accattato et al ( 2017 ) established a single bout of endurance exercise (20 min run at 70% VO 2peak ) acutely suppresses EGF in younger individuals, yet resistance training has been shown to acutely increase EGF in healthy trained men (Diaz-Castro et al 2020 ). Thus, it is clear the type of exercise (resistance vs endurance) influences EGF response after a period of training as recent studies in C2C12 myotubes have shown that EGF receptor inhibition promotes a slow twitch (oxidative) over a fast-twitch muscle phenotype (Ciano et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…> 1 month) on EGF in older men. However, Accattato et al ( 2017 ) established a single bout of endurance exercise (20 min run at 70% VO 2peak ) acutely suppresses EGF in younger individuals, yet resistance training has been shown to acutely increase EGF in healthy trained men (Diaz-Castro et al 2020 ). Thus, it is clear the type of exercise (resistance vs endurance) influences EGF response after a period of training as recent studies in C2C12 myotubes have shown that EGF receptor inhibition promotes a slow twitch (oxidative) over a fast-twitch muscle phenotype (Ciano et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite the beneficial effects of moderate and regular physical exercise, strenuous exercise, defined as any activity that expends six metabolic equivalents (METS) per minute or more [ 93 ], may become detrimental. In particular, Simon H.B.’s review [ 94 ] underscores how repetitive intense exercise may have deleterious cardiovascular effects, causing structural damage to muscle cells, leading to muscle soreness, swelling, prolonged loss of muscle function, increased ROS production, induction of pro-inflammatory signaling, impairment of immune functions and leakage of muscle proteins into circulation [ 95 , 96 ]. In these overtraining conditions, subjected to individual training capacity and fitness level, CoQ supplementation as a mitochondrial nutrient, and in particular ubiquinol, due to its antioxidant activity, may modulate these harmful responses.…”
Section: Muscle Health and Physical Exercisementioning
confidence: 99%
“…In addition to forming a key component of the body’s anti-oxidant system, CoQ may reduce the activation of NfκB by free radicals, thereby acting as a brake on chronic inflammation which is progressively relaxed as CoQ levels decline with age [ 127 ]. Some genetic defects in CoQ synthesis lead paradoxically to an increased life span [ 128 ] which is possibly due to mitohormesis, where production of a certain level of ROS initiates upregulation of antioxidant defenses to a degree that the overall benefit is greater than the damage sustained by the increased ROS [ 129 ].…”
Section: Biochemistry Of Mitochondrial Ageingmentioning
confidence: 99%